Inorganic composite phase change energy storage concrete material and preparation method thereof

The inorganic composite phase change energy storage concrete material addresses freeze-thaw resistance and mechanical weaknesses by using inorganic microcapsules and a modified water reducer, resulting in improved durability and strength.

CN119118593APending Publication Date: 2024-12-13INSTITUTE OF APPLIED CHEMISTRY JIANGXI ACADEMY OF SCIENCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411247371.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing concrete materials exhibit poor freeze-thaw resistance and mechanical properties, particularly in high-latitude seasonal frozen soil areas, leading to structural damage and reduced service life.

Method used

A method for preparing an inorganic composite phase change energy storage concrete material using cement, inorganic composite phase change microcapsules, natural coarse aggregate, air entraining agent, and a modified water reducing agent, where the microcapsules replace fine aggregate and incorporate a unique esterified monomer and addition polymerization to enhance mechanical properties and freeze-thaw resistance.

Benefits of technology

The concrete material demonstrates improved mechanical properties and enhanced freeze-thaw resistance, with the microcapsules providing heat storage performance and a clear core-shell structure that reduces porosity and permeability, while the modified water reducer enhances dispersibility and water reduction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an inorganic composite phase change energy storage concrete material and a preparation method thereof, belongs to the technical field of concrete materials, and is used for solving the technical problems of poor freeze-thaw resistance and mechanical property of a common concrete material in the prior art. The inorganic composite phase-change micro-capsule cement comprises cement, inorganic composite phase-change micro-capsules, natural coarse aggregate, an air entraining agent and a modified water reducing agent, and is prepared by taking a phase-change material paraffin, fly ash, diatomite and expanded perlite mixture as a core material and a compound of organic modified apatite and polymethyl methacrylate as a wall material. The prepared inorganic composite phase change microcapsule not only has excellent heat storage performance and continuous freeze-thaw resistance, but also has excellent mechanical properties, and can replace fine aggregate in a concrete material, and a modified water reducing agent prepared by addition polymerization of multiple monomers has the advantages of high water reducing rate and good dispersity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials, and in particular relates to an inorganic composite phase-change energy storage concrete material and a preparation method thereof. Background Art

[0002] In the field of construction engineering, concrete is a building material with strong adaptability. Ordinary concrete is made by mixing cement, sand and gravel and other aggregates with water. Concrete has high strength and durability, and its material source is wide. It has been widely used by people nowadays.

[0003] In cold regions, especially in high-latitude seasonal frozen soil areas, the temperature difference between day and night is large, and many constructed concrete structures are often damaged by repeated freeze-thaw cycles, resulting in cracking and damage on the concrete surface, thereby reducing the service performance of the concrete structure and significantly shortening its service life. The use of phase change materials in building materials can reduce the deterioration of concrete pavements caused by drastic temperature changes and solve the problem of frost resistance and durability of concrete materials caused by freeze-thaw cycles.

[0004] Patent application CN112592109A discloses a recycled concrete with excellent performance. When preparing fine aggregate, hydrophilic modified nano-silica sol and chitosan can penetrate into the smaller gaps inside the recycled aggregate, thereby improving the stability of the overall structure of the recycled aggregate; however, the above-mentioned prior art only improves the mechanical properties of the prepared recycled concrete, and cannot improve its own freeze-thaw resistance.

[0005] Patent application CN115340333A discloses a preparation and application of a green recycled concrete phase change material, which is to incorporate a polyethylene glycol series phase change material into recycled concrete fine aggregate to prepare a phase change composite material A, and then evenly mix the phase change composite material A and recycled concrete powder B to prepare a green recycled concrete phase change material; however, the polyethylene glycol series phase change material is an organic phase change material, which is directly doped into the recycled concrete material, and it is not easy to improve the stability of the phase change material, and it is impossible to make the prepared concrete material have a lasting anti-freeze-thaw performance;

[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an inorganic composite phase change energy storage concrete material, so as to solve the technical problems in the prior art that ordinary concrete materials have short freeze-thaw resistance and poor mechanical properties.

[0008] The objective of the present invention can be achieved by the following technical scheme: an inorganic composite phase change energy storage concrete material comprises the following components in parts by weight: 1000 parts of cement, 50-100 parts of inorganic composite phase change microcapsules, 500-700 parts of natural coarse aggregate, 1-2 parts of air entraining agent and 110-120 parts of modified water reducing agent.

[0009] The concrete material prepared by the invention comprises cement, inorganic composite phase change microcapsules, natural coarse aggregate, air entraining agent and modified water reducing agent; wherein the inorganic composite phase change microcapsules are used to replace fine aggregate, and basalt crushed stone with a particle size of 15-20 mm is used as natural coarse aggregate.

[0010] Furthermore, the modified water reducing agent is prepared by the following steps:

[0011] S1. Mix monomethoxy polyethylene glycol, water-carrying agent cyclohexane and catalyst p-toluenesulfonic acid and add them to a reaction kettle, then add acrylic acid, and react at a constant temperature of 110-120° C. for 5-6 hours to obtain an esterification product; precipitate the esterification product with ethanol to obtain a purified product; and dry the purified product at 60° C. to a constant weight to obtain an esterification monomer;

[0012] In the present invention, polymer monomethoxy polyethylene glycol and acrylic acid undergo esterification reaction to obtain an esterification monomer containing unsaturated double bonds. In the esterification reaction process, p-toluenesulfonic acid is used as a catalyst and cyclohexane is used as a water-carrying agent to obtain an esterification product. The esterification product is subjected to post-process treatment to obtain an esterification monomer after impurity removal and purification.

[0013] The reaction formula for preparing the esterification monomer by reacting monomethoxy polyethylene glycol and acrylic acid is as follows:

[0014]

[0015] The n value in the monomethoxy polyethylene glycol is 20-40.

[0016] S2, the esterification monomer, sodium allyl sulfonate and deionized water are mixed evenly to obtain monomer liquid A; the initiator ammonium persulfate and deionized water are mixed evenly to obtain an initiator solution; maleic anhydride and deionized water are mixed evenly to obtain monomer liquid B; the monomer liquid A and the initiator solution are added dropwise to the monomer liquid B within 1-2 hours, and then the temperature is raised to 75-85°C, and the reaction is continued for 2-3 hours to obtain a mixed product;

[0017] Maleic anhydride and deionized water undergo a hydrolysis reaction to obtain maleic acid, which is monomer liquid B.

[0018] The hydrolysis reaction of maleic anhydride is as follows:

[0019]

[0020] With ammonium persulfate as an initiator, an esterified monomer containing an unsaturated double bond, sodium allyl sulfonate and monomer liquid B undergo addition polymerization to prepare a modified water reducing agent.

[0021] The reaction formula for the addition polymerization of the esterified monomer, sodium allyl sulfonate and monomer liquid B is as follows:

[0022]

[0023] S3. The mixed product is naturally cooled to room temperature, the pH value of the mixed product is adjusted to 6-7 with a 0.1 mol / L NaOH solution, and then the mixed product is distilled under reduced pressure to evaporate all the deionized water to obtain an organic liquid modified water reducer.

[0024] Furthermore, in step S1, the usage ratio of monomethoxy polyethylene glycol, cyclohexane, p-toluenesulfonic acid, hydroquinone and acrylic acid is 25g:1-2g:1-2g:2g:7-15g.

[0025] Furthermore, in step S2, the usage ratio of the esterification monomer, sodium allyl sulfonate and deionized water is 30g:14-20g:100mL; the usage ratio of ammonium persulfate and deionized water is 11g:50mL; and the usage ratio of maleic anhydride and deionized water is 5-15g:50mL.

[0026] Furthermore, the method for preparing the inorganic composite phase change microcapsules comprises the following steps:

[0027] A1. Distearyl dimethyl ammonium chloride and deionized water are mixed, added to a water bath constant temperature oscillator, and oscillated at 60° C. for 1 hour to obtain an aqueous solution of quaternary ammonium salt; apatite is then added to the aqueous solution of quaternary ammonium salt, and the mixture is oscillated for 2-3 hours, centrifuged, and filtered to obtain a solid; the solid is washed with deionized water and vacuum dried to constant weight to obtain a modified solid; the modified solid is ground through a 300 mesh sieve to obtain an organically modified apatite;

[0028] A2, mixing and evenly stirring the organically modified apatite, polymethyl methacrylate and deionized water to obtain an apatite-modified polymethyl methacrylate solution;

[0029] A3, fly ash, diatomaceous earth, expanded perlite and paraffin are mixed and ground to obtain a composite inorganic powder with a particle size of 30-40 μm;

[0030] A4. Add the apatite-modified polymethyl methacrylate solution dropwise into the composite inorganic powder, mix and stir for 1-2 hours, and then dry at room temperature to constant weight to obtain inorganic composite phase change microcapsules.

[0031] Furthermore, in step A1, the usage ratio of distearyl dimethyl ammonium chloride, deionized water and apatite is 20-30 g:100 mL:10-20 g; in step A2, the usage ratio of organically modified apatite, polymethyl methacrylate and deionized water is 10-20 g:50 g:200 mL.

[0032] Furthermore, in step A3, the usage ratio of fly ash, diatomaceous earth, expanded perlite and paraffin is 5g:5g:5g:15-25g; in step A4, the usage ratio of apatite-modified polymethyl methacrylate solution and composite inorganic powder is 5-10g:50-60g.

[0033] Furthermore, the inorganic composite phase change energy storage concrete material is prepared by the following steps:

[0034] B1. Evenly mix water, cement, inorganic composite phase change microcapsules, natural coarse aggregate and air entraining agent to obtain a mixture; evenly mix the modified water reducer and water to obtain a diluted modified water reducer;

[0035] B2. Evenly mix the mixture with the diluted modified water reducing agent, transfer it into a mold, and mold it in a vacuum oven at room temperature for 3 days to obtain an inorganic composite phase change energy storage concrete material.

[0036] Furthermore, the natural coarse aggregate is basalt crushed stone with a particle size of 15-20 mm; the air entraining agent is sodium alkylbenzene sulfonate; the dosage ratio of water, cement, inorganic composite phase change microcapsules, natural coarse aggregate and air entraining agent is 300g:1000g:50-100g:500-700g:1-2g; the dosage ratio of modified water reducer and water is 10-20g:100g.

[0037] The present invention has the following beneficial effects:

[0038] 1. The concrete material prepared by the present invention comprises cement, natural coarse aggregate, inorganic composite phase change microcapsules, air entraining agent and modified water reducing agent; the cement used in the present invention is ordinary silicate cement; the natural coarse aggregate is specifically natural basalt coarse stone with a particle size of 15-20 mm; the air entraining agent is sodium alkylbenzene sulfonate, and the air entraining agent can make many tiny bubbles evenly distributed in the concrete. When the water in the concrete freezes and expands in volume, these bubbles can reduce the pressure generated by the volume expansion, thereby improving the antifreeze performance of the concrete; the present invention replaces the fine aggregate component in the cement with inorganic composite phase change microcapsules; the crystal structure of hydroxyapatite is hexagonal system or monoclinic system, and hydroxyapatite has internal The three-dimensional through-channel structure that is interconnected with the outside has a large exchangeable cation capacity between layers, which enables distearyl dimethyl ammonium chloride to enter the apatite layer, thereby obtaining organically modified apatite, further improving the mechanical properties and biocompatibility of the prepared apatite; polymethyl methacrylate is used as the wall material of the inorganic composite phase change microcapsule, and by combining the organically modified apatite as a bioactive filler with polymethyl methacrylate, a composite material of organically modified apatite and polymethyl methacrylate can be prepared, thereby improving the mechanical properties of the wall material polymethyl methacrylate; the organic-inorganic composite wall material has excellent mechanical properties, avoiding the breakage of the inorganic composite phase change microcapsule when used in cement. The present invention uses a mixture of fly ash, diatomaceous earth, expanded perlite and paraffin as the core material and apatite-modified polymethyl methacrylate as the wall material. The prepared inorganic composite phase change microcapsules not only have excellent heat storage performance but also have a clear core-shell structure. The protective effect of the shell layer prevents the core material from slowly oxidizing or chemically reacting. In addition, the inorganic composite phase change microcapsules can replace the original fine aggregate and play a role in reducing the porosity and permeability of concrete.

[0039] 2. Monomethoxy polyethylene glycol and acrylic acid undergo esterification reaction to prepare an esterified monomer containing unsaturated double bonds and aliphatic long chains; maleic anhydride is hydrolyzed to obtain an aqueous solution of maleic acid, namely monomer liquid B, thereby introducing a carboxyl functional group into the prepared modified water reducer; under the action of an initiator, the esterified monomer, sodium allyl sulfonate and monomer liquid B undergo addition polymerization reaction to prepare a modified water reducer. The modified water reducer prepared by the present invention is specifically a polycarboxylic acid water reducer, which has the advantage of high water reduction efficiency. The main chain containing sulfonic acid group, carboxyl group and aliphatic long chain constitutes a unique comb-like structure of the modified water reducer; the above-mentioned multifunctional groups and aliphatic long chains enable the synthesized modified water reducer to form an adsorption layer of a certain thickness on the cement surface. When these adsorption layers overlap and attract each other, a certain steric hindrance will be generated, so that it has excellent dispersibility in concrete and improves its own water reduction efficiency; in addition, the polycarboxylic acid water reducer has the advantages of being green and environmentally friendly. Cement, inorganic composite phase change microcapsules, modified water reducing agent, natural coarse aggregate and the like are mixed and formed to prepare an inorganic composite phase change energy storage concrete material with high strength, self-compacting and high water reducing rate. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] This embodiment provides a method for preparing inorganic composite phase change microcapsules for inorganic composite phase change energy storage concrete materials, comprising the following steps:

[0043] A1. Add 20 g of distearyl dimethyl ammonium chloride and 100 mL of deionized water into a 250 ml conical flask, then place the conical flask in a water bath constant temperature oscillator at 60° C., and oscillate at 200 r / min for 1 hour to obtain an aqueous solution of quaternary ammonium salt; then add 10 g of apatite into the conical flask, continue to oscillate at 100 r / min for 2 hours, then centrifuge and filter to obtain a solid; wash the solid three times with deionized water, and then dry in a vacuum oven at 80° C. to constant weight to obtain a modified solid; grind the modified solid through a 300 mesh sieve to obtain an organically modified apatite.

[0044] A2. Add 10 g of organically modified apatite, 50 g of polymethyl methacrylate and 200 mL of deionized water into a beaker, mix and stir evenly to obtain an apatite-modified polymethyl methacrylate solution.

[0045] A3. Add 5 g of fly ash, 5 g of diatomaceous earth, 5 g of expanded perlite and 15 g of paraffin into a planetary ball mill and grind to obtain a composite inorganic powder with a particle size of 30 μm; add 5 g of apatite-modified polymethyl methacrylate solution dropwise to 50 g of the composite inorganic powder, use an electric stirrer to mix and stir at 100 r / min for 1 h, and then dry to constant weight at room temperature to obtain inorganic composite phase change microcapsules.

[0046] Example 2

[0047] This embodiment provides a method for preparing inorganic composite phase change microcapsules for inorganic composite phase change energy storage concrete materials, comprising the following steps:

[0048] A1. Add 25g of distearyl dimethyl ammonium chloride and 100mL of deionized water into a 250ml conical flask, then place the conical flask in a water bath constant temperature oscillator at 60°C, and oscillate at 200r / min for 1h to obtain an aqueous solution of quaternary ammonium salt. Then add 13g of apatite into the conical flask, continue to oscillate at 100r / min for 2.5h, then centrifuge and filter to obtain a solid; wash the solid three times with deionized water, then dry in a vacuum oven at 80°C to constant weight to obtain a modified solid; grind the modified solid through a 300-mesh sieve to obtain an organically modified apatite.

[0049] A2. Add 15 g of organically modified apatite, 50 g of polymethyl methacrylate and 200 mL of deionized water into a beaker, mix and stir evenly to obtain an apatite-modified polymethyl methacrylate solution.

[0050] A3. Add 5 g of fly ash, 5 g of diatomaceous earth, 5 g of expanded perlite and 20 g of paraffin into a planetary ball mill and grind to obtain a composite inorganic powder with a particle size of 30 μm; add 8 g of apatite-modified polymethyl methacrylate solution dropwise to 55 g of the composite inorganic powder, use an electric stirrer to mix and stir at 100 r / min for 1.3 h, and then dry to constant weight at room temperature to obtain inorganic composite phase change microcapsules.

[0051] Example 3

[0052] This embodiment provides a method for preparing inorganic composite phase change microcapsules for inorganic composite phase change energy storage concrete materials, comprising the following steps:

[0053] A1. Add 30g of distearyl dimethyl ammonium chloride and 100mL of deionized water into a 250ml conical flask, then place the conical flask in a water bath constant temperature oscillator at 60°C, and oscillate at 200r / min for 1h to obtain an aqueous solution of quaternary ammonium salt. Then add 20g of apatite into the conical flask, continue to oscillate at 100r / min for 3h, then centrifuge and filter to obtain a solid; wash the solid three times with deionized water, then dry in a vacuum oven at 80°C to constant weight to obtain a modified solid; grind the modified solid through a 300-mesh sieve to obtain an organically modified apatite.

[0054] A2. Add 20 g of organically modified apatite, 50 g of polymethyl methacrylate and 200 mL of deionized water into a beaker, mix and stir evenly to obtain an apatite-modified polymethyl methacrylate solution.

[0055] A3. Add 5 g of fly ash, 5 g of diatomaceous earth, 5 g of expanded perlite and 25 g of paraffin into a planetary ball mill and grind to obtain a composite inorganic powder with a particle size of 30 μm; add 10 g of apatite-modified polymethyl methacrylate solution dropwise to 60 g of the composite inorganic powder, use an electric stirrer to mix and stir at 100 r / min for 2 h, and then dry to constant weight at room temperature to obtain inorganic composite phase change microcapsules.

[0056] Example 4

[0057] This embodiment provides a method for preparing a modified water reducing agent for an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0058] S1. Add 25 g of monomethoxy polyethylene glycol, 1 g of cyclohexane with water and 1 g of p-toluenesulfonic acid as catalyst into a reaction kettle and mix, then add 7 g of acrylic acid, accompanied by mechanical stirring at 100 r / min, and react at a constant temperature of 110° C. for 5 hours to obtain an esterification product; precipitate the esterification product with ethanol to obtain a purified product; transfer the purified product to a vacuum drying oven at 60° C. and dry to constant weight to obtain an esterification monomer.

[0059] S2. Mix 30 g of esterification monomer, 14 g of sodium allyl sulfonate and 100 mL of deionized water to obtain monomer liquid A; mix 11 g of initiator ammonium persulfate and 50 mL of deionized water to obtain an initiator solution; mix 5 g of maleic anhydride and 50 mL of deionized water to obtain monomer liquid B; add monomer liquid A and initiator solution drop by drop into monomer liquid B within 1 hour, then heat to 75°C, continue to react for 2 hours, and obtain a mixed product.

[0060] S3. The mixed product is naturally cooled at room temperature, the pH value of the mixed product is adjusted to 6 with a 0.1 mol / L NaOH solution, and then the mixed product is distilled under reduced pressure to evaporate all the deionized water solvent to obtain an organic liquid modified water reducer.

[0061] Example 5

[0062] This embodiment provides a method for preparing a modified water reducing agent for an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0063] S1. 25 g of monomethoxy polyethylene glycol, 2 g of cyclohexane with water, 2 g of p-toluenesulfonic acid as a catalyst and 2 g of hydroquinone as an inhibitor are mixed and added into a reactor, and then 10 g of acrylic acid is added. The mixture is reacted at a constant temperature of 115° C. for 5.5 h accompanied by mechanical stirring at 100 r / min to obtain an esterification product; the esterification product is precipitated with ethanol to obtain a purified product; the purified product is transferred to a vacuum drying oven at 60° C. and dried to constant weight to obtain an esterification monomer.

[0064] S2. Mix 30 g of esterification monomer, 18 g of sodium allyl sulfonate and 100 mL of deionized water to obtain monomer liquid A; mix 11 g of initiator ammonium persulfate and 50 mL of deionized water to obtain an initiator solution; mix 10 g of maleic anhydride and 50 mL of deionized water to obtain monomer liquid B; add monomer liquid A and the initiator solution drop by drop into monomer liquid B within 1.5 hours, then heat to 80°C, continue to react for 2.5 hours, and obtain a mixed product.

[0065] S3. The mixed product is naturally cooled at room temperature, the pH value of the mixed product is adjusted to 6.6 with 0.1 mol / L NaOH solution, and then the mixed product is distilled under reduced pressure to evaporate all the deionized water solvent to obtain an organic liquid modified water reducer.

[0066] Example 6

[0067] This embodiment provides a method for preparing a modified water reducing agent for an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0068] S1. 25 g of monomethoxy polyethylene glycol, 2 g of cyclohexane with water, 2 g of p-toluenesulfonic acid as a catalyst and 2 g of hydroquinone as an inhibitor are mixed and added into a reactor, and then 15 g of acrylic acid is added. The mixture is reacted at a constant temperature of 120° C. for 6 h accompanied by mechanical stirring at 100 r / min to obtain an esterification product; the esterification product is precipitated with ethanol to obtain a purified product; the purified product is transferred to a vacuum drying oven at 60° C. and dried to constant weight to obtain an esterification monomer.

[0069] S2. Mix 30 g of esterification monomer, 20 g of sodium allyl sulfonate and 100 mL of deionized water to obtain monomer liquid A; mix 11 g of initiator ammonium persulfate and 50 mL of deionized water to obtain an initiator solution; mix 15 g of maleic anhydride and 50 mL of deionized water to obtain monomer liquid B; add monomer liquid A and the initiator solution drop by drop into monomer liquid B within 2 hours, then heat to 85°C, continue to react for 3 hours, and obtain a mixed product.

[0070] S3. The mixed product is naturally cooled at room temperature, the pH value of the mixed product is adjusted to 7 with a 0.1 mol / L NaOH solution, and then the mixed product is distilled under reduced pressure to evaporate all the deionized water solvent to obtain an organic liquid modified water reducer.

[0071] Example 7

[0072] This embodiment provides a method for preparing an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0073] B1, 300g of water, 1000g of cement, 50g of the inorganic composite phase change microcapsules prepared in Example 1, and basalt crushed stone with a particle size of 15mm as natural coarse aggregate, 500g of natural coarse aggregate and 1g of air entraining agent are mixed uniformly to obtain a mixture; 10g of the modified water reducer prepared in Example 4 and 100g of water are stirred at 100r / min for 30min to obtain a diluted modified water reducer.

[0074] B2. The mixture was mixed with the diluted modified water reducing agent at 500 r / min and stirred for 3 h, then transferred to a mold and molded in a vacuum oven at room temperature for 3 days to obtain an inorganic composite phase change energy storage concrete material.

[0075] Example 8

[0076] This embodiment provides a method for preparing an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0077] B1, 300g of water, 1000g of cement, 70g of the inorganic composite phase change microcapsules prepared in Example 2, basalt crushed stone with a particle size of 15mm as natural coarse aggregate, 600g of natural coarse aggregate and 2g of air entraining agent are mixed uniformly to obtain a mixture; 15g of the modified water reducer prepared in Example 5 and 100g of water are stirred at 100r / min for 30min to obtain a diluted modified water reducer.

[0078] B2. The mixture was mixed with the diluted modified water reducing agent at 500 r / min and stirred for 4 h, then transferred to a mold and formed in a vacuum oven at room temperature for 3 days to obtain an inorganic composite phase change energy storage concrete material.

[0079] Example 9

[0080] This embodiment provides a method for preparing an inorganic composite phase change energy storage concrete material, comprising the following steps:

[0081] B1, 300g of water, 1000g of cement, 100g of the inorganic composite phase change microcapsules prepared in Example 3, basalt crushed stone with a particle size of 15mm as natural coarse aggregate, 700g of natural coarse aggregate and 2g of air entraining agent are mixed uniformly to obtain a mixture; 20g of the modified water reducer prepared in Example 6 and 100g of water are stirred at 100r / min for 30min to obtain a diluted modified water reducer.

[0082] B2. The mixture was then mixed and stirred with the diluted modified water reducing agent at 500 r / min for 5 hours, and then transferred to a mold and molded in a vacuum oven at room temperature for 3 days to obtain an inorganic composite phase change energy storage concrete material.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 9 is that when preparing the inorganic composite phase change microcapsules, polymethyl methacrylate is not composited with the organic modified apatite.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 9 is that when preparing the inorganic composite phase-change microcapsules, the composite inorganic powder is replaced by paraffin wax of equal mass.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 9 is that no esterification monomer is added when preparing the modified water reducing agent.

[0089] Performance Testing:

[0090] 1. According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the inorganic composite phase change energy storage concrete materials prepared in Examples 7-9 were subjected to a rapid freeze-thaw cycle test using a programmed ultra-low temperature testing machine. After 200 freeze-thaw cycle tests, the strength value was measured as a percentage of the original strength value.

[0091] 2. According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the water absorption rate of the inorganic composite phase change energy storage concrete material prepared in Examples 7-9 was measured, wherein the water absorption time was 8h.

[0092] 3. According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the compressive strength of the inorganic composite phase change energy storage concrete materials prepared in Examples 7-9 was measured.

[0093] The test results are shown in Table 1:

[0094] Table 1 - Performance test data table

[0095]

[0096] Data Analysis:

[0097] The inorganic composite phase change energy storage concrete materials prepared in Examples 7-9 of the present invention have excellent latent heat storage characteristics, which is manifested in that the inorganic composite phase change energy storage concrete materials prepared in Examples 7-9 have excellent freeze-thaw resistance. After 200 freeze-thaw cycle tests, the decrease in strength value is slightly lower; in Comparative Example 2, when preparing inorganic composite phase change microcapsules, the composite inorganic powder is replaced by phase change material paraffin of the same mass, thereby improving its own freeze-thaw resistance, but its compressive strength and water absorption performance are both reduced.

[0098] The wall material of the inorganic composite phase change energy storage concrete material prepared in Examples 7-9 of the present invention and Comparative Examples 1-3 is made of polymethyl methacrylate, which contains polar side methyl groups and has strong hygroscopicity, so that the prepared inorganic composite phase change energy storage concrete material has strong hygroscopicity.

[0099] The inorganic composite phase change energy storage concrete materials prepared in Examples 7-9 of the present invention have excellent mechanical properties, which are manifested in their high compressive strength; however, in Comparative Example 1, when preparing the inorganic composite phase change microcapsules, polymethyl methacrylate was not compounded with organic modified apatite, thereby reducing the mechanical properties of the prepared inorganic composite phase change energy storage concrete material, which is manifested in a decrease in its own compressive strength value.

[0100] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0101] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0102] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. Inorganic composite phase change energy storage concrete material, characterized in that: The invention comprises the following components in parts by weight: 1000 parts of cement, 50-100 parts of inorganic composite phase change microcapsules, 500-700 parts of natural coarse aggregates, 1-2 parts of air entraining agent and 110-120 parts of modified water reducing agent.

2. The inorganic composite phase change energy storage concrete material according to claim 1, characterized in that: The modified water reducing agent is prepared by the following steps: S1, adding monomethoxy polyethylene glycol, water-carrying agent cyclohexane and catalyst p-toluenesulfonic acid to a reaction kettle, and then adding acrylic acid, and reacting at a constant temperature of 110-120° C. for 5-6 hours to obtain an esterification product; using ethanol to precipitate the esterification product to obtain a purified product; The purified product was dried at 60°C to constant weight to obtain an esterified monomer; S2, the esterification monomer, sodium allyl sulfonate and deionized water are mixed evenly to obtain monomer liquid A; the initiator ammonium persulfate and deionized water are mixed evenly to obtain an initiator solution; maleic anhydride and deionized water are mixed evenly to obtain monomer liquid B; the monomer liquid A and the initiator solution are added dropwise to the monomer liquid B within 1-2 hours, and then the temperature is raised to 75-85°C, and the reaction is continued for 2-3 hours to obtain a mixed product; S3. The mixed product is naturally cooled to room temperature, the pH value of the mixed product is adjusted to 6-7 with a 0.1 mol / L NaOH solution, and then the mixed product is distilled under reduced pressure to evaporate all the deionized water to obtain an organic liquid modified water reducer.

3. The inorganic composite phase change energy storage concrete material according to claim 2, characterized in that: In step S1, the usage ratio of monomethoxy polyethylene glycol, cyclohexane, p-toluenesulfonic acid, hydroquinone and acrylic acid is 25g:1-2g:1-2g:2g:7-15g.

4. The inorganic composite phase change energy storage concrete material according to claim 3, characterized in that: In step S2, the usage ratio of the esterification monomer, sodium allyl sulfonate and deionized water is 30g:14-20g:100mL; the usage ratio of ammonium persulfate and deionized water is 11g:50mL; and the usage ratio of maleic anhydride and deionized water is 5-15g:50mL.

5. The inorganic composite phase change energy storage concrete material according to claim 4, characterized in that: The method for preparing the inorganic composite phase-change microcapsules comprises the following steps: A1. Distearyl dimethyl ammonium chloride and deionized water are mixed, added to a water bath constant temperature oscillator, and oscillated at 60° C. for 1 hour to obtain an aqueous solution of quaternary ammonium salt; apatite is then added to the aqueous solution of quaternary ammonium salt, and the mixture is oscillated for 2-3 hours, centrifuged, and filtered to obtain a solid; the solid is washed with deionized water and vacuum dried to constant weight to obtain a modified solid; the modified solid is ground through a 300 mesh sieve to obtain an organically modified apatite; A2, mixing and uniformly stirring the organically modified apatite, polymethyl methacrylate and deionized water to obtain an apatite-modified polymethyl methacrylate solution; A3, fly ash, diatomaceous earth, expanded perlite and paraffin are mixed and ground to obtain a composite inorganic powder with a particle size of 30-40 μm; A4. Add the apatite-modified polymethyl methacrylate solution dropwise into the composite inorganic powder, mix and stir for 1-2 hours, and then dry at room temperature to constant weight to obtain inorganic composite phase change microcapsules.

6. The inorganic composite phase change energy storage concrete material according to claim 5, characterized in that: In step A1, the dosage ratio of distearyl dimethyl ammonium chloride, deionized water and apatite is 20-30 g:100 mL:10-20 g; in step A2, the dosage ratio of organically modified apatite, polymethyl methacrylate and deionized water is 10-20 g:50 g:200 mL.

7. The inorganic composite phase change energy storage concrete material according to claim 6, characterized in that: In step A3, the usage ratio of fly ash, diatomaceous earth, expanded perlite and paraffin is 5g:5g:5g:15-25g; in step A4, the usage ratio of apatite-modified polymethyl methacrylate solution and composite inorganic powder is 5-10g:50-60g.

8. The inorganic composite phase change energy storage concrete material according to claim 7, characterized in that: In step A4, the usage ratio of CaCl2 and DMF is 10-20 g:100 mL; the usage ratio of NaCO3 and deionized water is 10 g:50 mL.

9. The method for preparing the inorganic composite phase change energy storage concrete material according to claim 8, characterized in that: The inorganic composite phase change energy storage concrete material is prepared by the following steps: B1. Evenly mix water, cement, inorganic composite phase change microcapsules, natural coarse aggregate and air entraining agent to obtain a mixture; evenly mix the modified water reducer and water to obtain a diluted modified water reducer; B2. Evenly mix the mixture with the diluted modified water reducing agent, transfer it into a mold, and mold it in a vacuum oven at room temperature for 3 days to obtain an inorganic composite phase change energy storage concrete material.

10. The method for preparing the inorganic composite phase change energy storage concrete material according to claim 9, characterized in that: The natural coarse aggregate is basalt crushed stone with a particle size of 15-20 mm; the air entraining agent is sodium alkylbenzene sulfonate; the dosage ratio of water, cement, inorganic composite phase change microcapsule, natural coarse aggregate and air entraining agent is 300g:1000g:50-100g:500-700g:1-2g; the dosage ratio of modified water reducing agent and water is 10-20g:100g.

Citation Information

Cited By

  • Building waste environment-friendly water stabilizing material as well as preparation method and application thereof

    CN120647211A

  • Alkali-activated phase change heat storage concrete with self-repairing function and preparation method of alkali-activated phase change heat storage concrete

    CN121270153A